2018
DOI: 10.1302/1863-2548.12.170197
|View full text |Cite
|
Sign up to set email alerts
|

Foot and ankle deformities in children with down syndrome

Abstract: PurposeFoot and ankle deformities are common orthopaedic disorders in children with Down syndrome. However, radiographic measurements of the foot and ankle have not been previously reported. The aim of this study is to describe the foot and ankle deformity in children with Down syndrome.MethodsChildren who had foot and ankle radiographs in the standing weight-bearing position were selected. Three groups of patients were identified. The relationship of radiographic measurements with age, body mass index and pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 34 publications
(51 reference statements)
4
22
0
Order By: Relevance
“…The radiographic studies about the foot structure in DS children with pes planus showed large talo first-metatarsal angle, low navicular height and calcaneal inclination angle in their feet revealing abnormal alignment of the talonavicular and calcaneocuboid joint [5,6].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The radiographic studies about the foot structure in DS children with pes planus showed large talo first-metatarsal angle, low navicular height and calcaneal inclination angle in their feet revealing abnormal alignment of the talonavicular and calcaneocuboid joint [5,6].…”
Section: Introductionmentioning
confidence: 97%
“…The radiographic studies about the foot structure in DS children with pes planus showed large talo first-metatarsal angle, low navicular height and calcaneal inclination angle in their feet revealing abnormal alignment of the talonavicular and calcaneocuboid joint [5,6]. Some studies pointed out that the ligament laxity and hypotonia caused by genetic issue are the main reasons for DS children's pes planus which induce abnormal alignment of foot [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This is most evident in the lower limb where it is possible to detect, a valgism of the knees associated with pronation and flatness of the foot (about 58%). (Volman et al 2007;Perotti et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Flat foot is also a common orthopedic complaint for patients with Down syndrome [1]. A previous radiographic study demonstrated that 58% of patients with Down syndrome have flat foot [2]. It is well known that the foot arch supports the body weight and decentralizes plantar pressure.…”
Section: Introductionmentioning
confidence: 99%
“…These physical problems can cumulatively result in a decline in gait function. The incidence of flat foot for patients with Down syndrome is estimated to be 27.0-58.0% [2,6]; 88.9% of these patients are treated with insole insertions [6]. It is known that inserting an insole as a treatment method for a flat foot is important and commonly used.…”
Section: Introductionmentioning
confidence: 99%